Science Learning Through Experimentations - Pandey, D. K. (SCHOOL SCIENCE, 2017)
One of the success stories of the ‘National Children's Science Congress’ — a mega event initiated and organised annually by Department of Science and Technology, Government of India— is that students get themselves involved in finding feasible solutions of some context specific issues, with great excitements. Learning microbiology without support of sophisticated equipment is not easy. Efforts were made to develop such a module on ‘Microbiology’, which is very easy to handle and can demonstrate nearly 40 experiments even at classroom situations. Before delivery of a lecture, if we conduct experiments in front of students the subjects become interesting and students are able to ask the questions. This is the beauty of learning science with experiments. The author was able to develop similar science learning modules in physics, chemistry, mathematics, biology, microbiology, astronomy, soil science, explaining science behind miracles, water and soil testing kit (Parkhee), etc. These modules were evaluated by students of B.Ed. and M.Ed courses of Delhi University. They found that these modules to be very useful.